Generic classification in the Cordiaceae (Boraginales): resurrection of the genus Varronia P. Br. - Miller, J.S.; Gottschling, M.
Modern authors have not agreed on a satisfactory system of generic delimitation among woody Boraginales. Recent treatments have recognized a broadly defined Cordia with 3-7 subgenera or sections. Molecular sequence data suggest an alignment of genera that is consistent with morphological and palynological data. In advance of publication of several major floristic studies on Boraginaceae, generic delimitation of the traditional Cordioideae is reviewed. Coldenia, formerly considered a member of Ehretioideae, is sister to Cordia s.l. Within Cordia s.l., Varronia is sister to the rest of the genus and its resurrection as a distinct genus is proposed. Thus defined, Cordiaceae comprise three genera, all of which are monophyletic and consistent with vegetative, floral, and pollen morphology.
Keywords: BORAGINACEAE; CORDIA; CORDIOIDEAE; TAXONOMY; VARRONIA